KEEFEKTIFAN PROGRAM PERILAKU CERDIK DENGAN KEJADIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TALISE - Rianti Rianti; Elifa Ihda Rahmayanti; Agnes Erlita Distriani Patade (Universitas Widya Nusantara, 2026)
CERDIK is a routine health check, free from cigarette smoke, routine exercise, balanced diet, adequate rest and stress management. Hypertension occurs when a person has a systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg on examination. Diastolic blood pressure is the main measurement in the diagnosis of hypertension. This research uses a quantitative study. Descriptive correlation by using a cross-sectional approach. Total of population was 50 people who have participated in the CERDIK program Individual. And by using conceptive sampling technique, 25 respondents were selected as the research sample. Based on the results of the spearman rank test with a correlation coefficient value = 0.555, it shows that the correlation between the two variables has a negative direction, it means that when the CERDIK behavior program is high, the degree of hypertension tends to low, so the strength is considered moderate, because the value is not reach to -1. strength is considered moderate, because the value is not too close to -1. The p-value of this study was 0.004, therefore the p-value was <0.05, so statistically there is an effectiveness of the CERDIK behavior program toward the incidence of hypertension in the Talise Public Health Center working area.The higher the CERDIK behavior, it is the better/low the incidence of hypertension in the Talise Public Health Center working area. the incidence of hypertension in the Talise Health Center working area For health workers should motivate and promote patients to follow the CERDIK behavior program in controlling/lowering hypertension.